Cobalt-57-bleomycin scanning of hila and mediastinum in patients with bronchial carcinoma: a prospective study. - Rasker, J J (1976)
Because the results with cobalt-57-bleomycin (57Co-bleo) as a tumour-seeking agent in patients with pulmonary tumours were promising, a prospective study was carried out to test the sensitivity and selectivity of this technique for metastases in lung hila and mediastinum in a group of patients with bronchial cancer. The sensitivity of 57Co-bleo scintigraphy appeared to be higher than that of routine radiological investigations and mediastinoscopy. For this reason it is suggested that 57Co-bleo scintigraphy can be used as a method to select patients for mediastinoscopy.